Frailty Before Critical Illness and Mortality for Elderly Medicare Beneficiaries. Issue 6 (June 2015) - Hope, Aluko A.; Gong, Michelle N.; Guerra, Carmen; Wunsch, Hannah
<x xml:space="preserve">Abstract</x> Objectives To estimate the effect of pre‐intensive care unit (ICU) health categories on mortality during and after critical illness, focusing specifically on the effect of pre‐ICU frailty on short‐ and long‐term mortality. Design Retrospective cohort study. Setting Medicare claims data from 2004 to 2008. Participants A nationally representative sample of elderly Medicare beneficiaries admitted to an ICU in 2005. Measurements Participants were classified into four pre‐ICU health categories (robust, cancer, chronic organ failure, frailty) using claims data from the year before admission, allowing for assignment to multiple categories. The association between pre‐ICU health category and hospital and 3‐year mortality was assessed using multivariable logistic regression and Cox proportional hazards models. Results Of 47, 427 elderly individuals in the ICU, 18.8% were robust, 28.6% had cancer, 68.1% had chronic organ failure, and 34.0% were frail; 41.3% qualified for multiple categories. Overall hospital mortality was 12.6%, with the lowest mortality for robust participants (9.7%). Participants with pre‐ICU frailty had higher hospital mortality than those with the same pre‐ICU health categories without frailty. (Adjusted odds ratios ranged from 1.27 (95% confidence interval (CI) 1.10–1.47) to 1.52 (95% CI = 1.35–1.63).) Robust hospital survivors had the lowest 3‐year mortality (24.6%). Pre‐ICU frailty conferred higher 3‐year mortality than pre‐ICU categories without frailty. (Adjusted hazard ratios ranged from 1.54 (95% CI = 1.45–1.64) to 1.84 (95% CI = 1.70–1.99).) Conclusion Critically ill elderly adults can be categorized according to pre‐ICU health categories. These categories, particularly pre‐ICU frailty, may be important for understanding risk of death during and after critical illness.